Application of Small Spacecraft for Automatic Identification of Vessels - Makarov, S. B.; Zavjalov, S. V.; Volvenko, S. V.; Lavrenyuk, I.; Gorbunov, I. N.; Vinnichenko, M. Ya.; Aharonyan, A. K.; Avetisyan, V. H.
The work is devoted to the development of a specialized complex based on a CubeSat 3U nanosatellite for receiving and processing signals from the AIS system. With the help of such system, it is planned to form a domestic AIS space constellation. The urgency is connected with the current absence of the Russian Federation’s own satellite means of obtaining AIS data for monitoring the movement of ships in the world’s oceans and in its own water area. Access to this data is becoming critical in connection with the development of the Northern Sea Route and the development of shipping in the Azov, Black Seas and the Far East.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture